Pengaruh Iklan, Citra Merek, dan Kepuasan Konsumen terhadap Loyalitas Konsumen Nivea For Men di Kota Banda Aceh - Rizal, Syamsul; Ismail (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study aims to analyze the impact of advertising, brand image, and customer satisfaction on customer loyalty to Nivea For Men in Banda Aceh. Customer loyalty is crucial in maintaining a brand's position in a competitive market. Advertising plays an important role in shaping consumer perceptions and purchase intentions, while brand image influences consumer trust and emotional attachment to the product. Customer satisfaction, stemming from positive product experiences, acts as a key factor in building loyalty. This research uses a quantitative approach with surveys to collect data from Nivea For Men consumers. Multiple linear regression analysis is employed to examine the relationships between these variables. The results show that advertising significantly influences customer loyalty, with brand image also having a notable impact. Customer satisfaction, driven by product and service quality, proves to be the most influential factor. These findings indicate that companies should strengthen their advertising strategies, maintain a consistent brand image, and enhance customer satisfaction to build long-term loyalty.